(untitled) (SCIÉNDO INGENIUM, 2021)
The objective is to determine the influence of artisanal and informal mining in the quality of water resources in Parcoy, La Libertad. The research was descriptive, correlational and transversal. In the conclusions it was identified that artisanal and informal gold mining is developed by 75%. There is contamination of 63,3% of heavy metals (arsenic, cadmium, copper, lead, zinc and iron) in the Balcones, Huinchus, Huariracra, Trancahuayco and Parcoy river ravines. Contamination was detected at pH level> 6, total dissolved solids> 500 mg / L, dissolved oxygen> 5 mg / L, conductivity <1500 uS / cm and turbidity> 5 NTU. A survey was applied to the Parcoy community and it was determined that 29,5% agree and 31,8% partially agree that mining activity pollutes water resources. It is concluded at the level of hypothesis testing that the correlation between the variable artisanal and informal mining and water resources was significant with a Pearson coefficient of 0,663 and the level of significance of 0,00 was less at the level of significance of 0,01 per which, the hypothesis raised is accepted.